2006
DOI: 10.1108/02686900610674898
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of auditor independence in Barbados

Abstract: Purpose-The study investigates the perceptions of auditor independence (PAI) between auditors and users in Barbados. Design/methodology/approach-A self-administered questionnaire was adapted and modified from Beattie et al.'s study in the UK the sample included 66 auditors and 148 users. Factors relating to the size and closeness of Barbadian society, lengthy tenure and being a sole audit practitioner, small audit firm, provision of non-audit services (NAS) among others, were investigated. Findings-Economic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
3
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 18 publications
12
77
3
13
Order By: Relevance
“…This finding is inconsistent with the reports of Abu Bakar et al (2005) and Alleyne and Devonish (2006) who found that individual non-audit services may affect auditor independence influence audit quality perceptions differently and that the provision of NAS is a significant threat to perceptions of auditor independence.…”
Section: The Perceptions Of Nas Based On Type Of Audit Firmscontrasting
confidence: 57%
See 1 more Smart Citation
“…This finding is inconsistent with the reports of Abu Bakar et al (2005) and Alleyne and Devonish (2006) who found that individual non-audit services may affect auditor independence influence audit quality perceptions differently and that the provision of NAS is a significant threat to perceptions of auditor independence.…”
Section: The Perceptions Of Nas Based On Type Of Audit Firmscontrasting
confidence: 57%
“…The potential for public perception of impaired auditor independence when a firm provides both audit and NAS is confirmed by several researchers (Hay et al, 2006;Simunic, 1984, Beck et al, 1988a, Canning and Gwilliam, 1999Craswell, 1999;Abu Bakar et al, 2005;Alleyne and Devonish, 2006), who note that the high fees involved suggest too great a mutual reliance between auditor and auditee. However, as noted by Mautz and Sharaf (1961) half a century ago, the interests of auditor and auditee become the same when both audit and NAS are provided, and this inevitably leads to an end to the accountant's independence.…”
Section: Arguments Against the Provision Of Non-audit Services (Nas)mentioning
confidence: 85%
“…Individuals may acquire experience through direct observation or participation in a particular event or activity (Alleyne et al, 2006). Experiences in work-related challenges expose auditors to gaining more confidence and competences in relation to making riskconnected decisions (Payne and Ramsay, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Krosnick & Fabrigar, 1997;Beattie, Brandt, & Fearnley, 1999) as being more reliable and not forcing the respondents to respond in a particular direction thereby increasing measurement error. This choice is also in line with prior interdependence studies examining perceptions of AI (e.g., Alleyne, Devonish, & Alleyne, 2006;Al-Ajmi & Saudagaran, 2011). The two dimensions examined are Independence in Fact (IIF) which is evaluated by three variables; Perceived objectivity, Perceived integrity and perceived Professional skepticism and Independence in appearance (IIA) which is evaluated by six variables; self interest, self review, familiarity, advocacy, intimidation and safeguard implementation.…”
Section: Measurements and Instrumentationmentioning
confidence: 60%